1988
DOI: 10.1038/bjc.1988.8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of 5-(3-methyl-1-triazeno)imidazole-4-carboxamide (MTIC) on Mer+, Mer+Rem- and Mer- cell lines: differential potentiation by 3-acetamidobenzamide

Abstract: Summary Mechanisms of resistance to the active metabolite 5-(3-methyl-1-triazeno)imidazole-4-carboxamide (MTIC) of the drug 5-(3,3-dimethyl-1-triazeno)imidazole-4-carboxamide (DTIC) were studied in three human cell lines with differing amounts of the repair enzyme 06-alkylguanine-DNA alkyltransferase (06AT). The lines were HT29 (Mer+Rem+), A549 (Mer+Rem-) and VA13 (Mer-). The ability to repair 06 methylguanine was directly related to resistance to MTIC (HT29 ID50 650 pmol -1, A549 ID50 210 pmol -1, VA1 3 ID50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Although the ability to form a monomethyl species is required for antitumour activity, this may not be the sole mechanism by which triazenes exert their in vivo antitumour activity (Gescher et al, 1981;Sava et al, 1988). Some Mer-cells are relatively sensitive to the monomethyl species of dacarbazine in vitro, but it is unclear whether this phenotype is a direct or indirect determinant of the lethal effects of triazenes (Gibson et al, 1986;Lunn & Harris, 1988). However, even if monomethyl metabolite formation is not the sole determinant of activity, a higher level might be expected to be associated with improved activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ability to form a monomethyl species is required for antitumour activity, this may not be the sole mechanism by which triazenes exert their in vivo antitumour activity (Gescher et al, 1981;Sava et al, 1988). Some Mer-cells are relatively sensitive to the monomethyl species of dacarbazine in vitro, but it is unclear whether this phenotype is a direct or indirect determinant of the lethal effects of triazenes (Gibson et al, 1986;Lunn & Harris, 1988). However, even if monomethyl metabolite formation is not the sole determinant of activity, a higher level might be expected to be associated with improved activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to the best of our knowledge, we could not find any primary data that would support the statement that MTIC is not able to penetrate cell membranes effectively. Several in vitro studies have shown that MTIC treatment of a variety of tumor cells (HeLa cells, colon carcinoma or lung adenocarcinoma cells, murine lymphoma cells) reduced cell viability as efficiently as DTIC and TMZ and induced DNA double strand breaks [84,85,86]. In those experiments, MTIC was simply added to the cell culture, thus it is likely that it is able to cross cell membranes in order to induce those biological effects.…”
Section: Open Questions Regarding Tmz’s Mode Of Actionmentioning
confidence: 99%
“…ATase is able to transfer the methyl group from the 06 position of guanine to an internal cysteine residue in an auto-inactivating stoichiometric reaction. Experimental models using ATase-deficient cell lines or xenografts show them to be more sensitive to DTIC than lines or xenografts with high activity (Hayward & Parsons, 1984;Gibson et al, 1986;Catapano et al, 1987;D'Incalci et al, 1988;Lunn & Harris, 1988;Foster et al, 1990). The strongest evidence for the cytotoxic effects of 06-alkylguanine in DNA comes from ATase cDNA transfection experiments which show that expression of prokaryotic or eukaryotic ATase cDNA in mammalian cells protects them against the toxic effects to these agents (Brennand & Margison, 1986;Kataoka et al, 1986;Samson et al, 1986;Kaina et al, 1991).…”
mentioning
confidence: 99%